MINORITY LANGUAGE RIGHTS - Yosefina Helenora Jem (Unika Santu Paulus Ruteng, 2017)
This article discusses some issues relating to minority language rights in general. This stems from the phenomenon of the language where English is used as the number one language in the world. Furthermore, in this article we explain the nature of minority language rights and their objectives as well as the grouping of minority language rights. Furthermore, there is also a link between language and education specifically in the education system in Indonesia.